Everything, all the time, everywhere how we became post-modern - Jeffries, Stuart 1962- (Verso, 2021)
"Where modernism was serious, absorbed in grand narratives and committed to social progress, its successor was a riot of colour and irreverence, toying with forms and styles, committed to none of them and to nothing. But beneath its glitzy surface, post-modernism hid a dirty secret: it was the fig leaf for a rapacious new kind of capitalism, the bridgehead of the 'post-truth' era in Western values"--
Keywords: Geschichte 1970-2021; Kultur; Kunst; Postmoderne; Postmodernism; PHILOSOPHY / General